An Analysis of Characteristics and Inhibition of Vaname Shrimp Chitosan on Streptococcus mutans - I Gusti Agung Ayu Dharmawati; Nyoman Mastra; Ni Nyoman Dewi Supariani; I Wayan Juniarsana (Humanistic Network for Science and Technology (HNST), 2022)
Indonesia is a maritime country with abundant marine products, but the processing of marine animal waste has not been a concern, the shell contains chitosan as a multifunctional biopolymer. Chitosan is a proven biomaterial that is non-toxic, biocompatible, and biodegradable compared to other polymers. The purpose of this study was to find out the content of Vaname shrimp chitosan and its inhibition against Streptococcus mutans bacteria. An experimental study was used, with a post test only control group design with the following treatments: control, 16 mg chitosan, 20 mg chitosan. Inhibitory power data (milli meter) was tested with One Way Anova. The research was carried out at the RAN Denpasar Laboratory, the Laboratory of the Faculty of Nutrition (Public Health, Airlangga University, Faculty of Pharmacy, Chemistry, Unair), UPT Analytical Laboratory Unud, and Microbiology Laboratory Unair. Results of this study indicated the content of carbohydrates, nitrogen, water, ash, protein, fat and the degree of deacetylation. Chitosan has an inhibitory effect on Streptococcus mutans bacteria. The quantity and quality of chitosan in Vaname shrimp, mets the requirements specified by Protan Biopolymer and was useful as an antimicrobial. Keywords: chitosan; vaname shrimp; characteristics; inhibition